Dental Paleopathology of the Ray Site (12W6), Indiana - Tammy R. Greene (Dental Anthropology Association, 2002)
The Ray site (1 2W6), in southern Indiana, contains several secondary burials, two of which have been dated to the Mississippian period (A.D. 1050-A.D. 1450). Three burial styles were noted: (1) burials lined with stone slabs and containing Mississippian pottery, (2) burials lined with stone slabs without Mississippian pottery, and (3) burials not lined with stone slabs and without Mississippian pottery. The purpose of this study was to determine the biological homogeneity of this poorly preserved skeletal assemblage via an analysis of dental pathological conditions, the frequency and expression of which are known to associate with distinct dietary and/or settlement patterns. Conditions studied include the frequency of hypoplastic defects and carious lesions, the type of hypoplastic defects, the earliest age of onset of hypoplastic defects, and the location of carious lesions. A total of 437 teeth were scored for hypoplastic defects and 433 were scored for carious lesions. No significant difference in dental pathologies was found between burial styles. Therefore, despite considerable burial heterogeneity, dental pathological conditions suggest that individuals from all burials consumed an equally cariogenic diet and underwent similar childhood stresses. It is most likely that all burials are from the same temporal and social group and that the different burial styles represent different stages in the processing of the remains of individuals from a high social status Mississippian mortuary.